2018
DOI: 10.1007/s12046-018-0848-4
|View full text |Cite
|
Sign up to set email alerts
|

New LSB-based colour image steganography method to enhance the efficiency in payload capacity, security and integrity check

Abstract: Steganography is the technique for hiding information within a carrier file so that it is imperceptible for unauthorized parties. In this study, it is intended to combine many techniques to gather a new method for colour image steganography to obtain enhanced efficiency, attain increased payload capacity, posses integrity check and security with cryptography at the same time. Proposed work supports many different formats as payload. In the proposed method, the codeword is firstly formed with secret data and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Main limitation of this work is stego analysis part has missed. It extends to that some other methods also using to enhance the capacity of payload embedding into images like LSB method as well as attacks on stegaanalysis [12][13].…”
Section: Preliminariesmentioning
confidence: 84%
“…Main limitation of this work is stego analysis part has missed. It extends to that some other methods also using to enhance the capacity of payload embedding into images like LSB method as well as attacks on stegaanalysis [12][13].…”
Section: Preliminariesmentioning
confidence: 84%
“…But repeated testing has shown that such substitution can carried out till 5 th least significant bit at maximum. After 5 th bit substitution, secret message starts revealing its existence which is against the objective of steganography [56]. An experiment has shown that in case of 24 bits' true color image, capacity of embedding secret image is 1/8th of the total size.…”
Section: Figure 1 Grey Level Representation In Histogram Of An Imagementioning
confidence: 99%
“…Digital watermarking is the process of embedding information into digital multimedia content such that the information (the watermark) can later be extracted or detected for a variety of purposes including copy prevention and control. Basically, it is advised to use the LSB approach [5] [7], which allows for a replacement that is not generally visible to the human eye; i.e. of less significance.…”
Section: Related Workmentioning
confidence: 99%
“…A steganography task is to hide a certain message in another container file, so that the presence of the hidden message cannot be seen [2,3]. As containers, digital images, audio and video files are commonly used [2,5,7]. As a result of embedding, steganography overcome the limitation of cryptography by hiding the fact that a transmission through the communication channel is taking place.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation